2021
DOI: 10.3389/fneur.2020.525621
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio and Platelet-to-Lymphocyte Ratio as Potential Predictors of Prognosis in Acute Ischemic Stroke

Abstract: Objective: Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) have been emerging as the novel inflammatory biomarkers for determining the prognosis of various diseases. This study aimed to investigate the individual and joint effects of NLR and PLR on functional outcomes of acute ischemic stroke (AIS).Methods: Our study involved 448 eligible patients with first-ever AIS. Clinical and laboratory data were collected on admission within 72 h from stroke onset. Unfavorable functional outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 41 publications
2
60
0
Order By: Relevance
“…Various studies have shown that NLR is closely related to AIS dysfunction, short-term mortality, stroke severity on admission, primary unfavorable functional outcome, recurrent ischemic stroke and post stroke infections, greater risk of symptomatic intracranial hemorrhage, poor 3-month functional outcome, and 3-month mortality in AIS patients undergoing reperfusion treatments, which is consistent with our results (Xue et al, 2017;Kocaturk et al, 2019;Chen et al, 2020;Giede-Jeppe et al, 2020;He et al, 2020;AltinbaŞ et al, 2021;Bi et al, 2021;Ferro et al, 2021;Gong et al, 2021;Hu et al, 2021;Huang et al, 2021;Lin et al, 2021). In a recent study, NLR ≥ 9 was an independent predictor of new in-hospital neurologic complications (Heuschmann et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Various studies have shown that NLR is closely related to AIS dysfunction, short-term mortality, stroke severity on admission, primary unfavorable functional outcome, recurrent ischemic stroke and post stroke infections, greater risk of symptomatic intracranial hemorrhage, poor 3-month functional outcome, and 3-month mortality in AIS patients undergoing reperfusion treatments, which is consistent with our results (Xue et al, 2017;Kocaturk et al, 2019;Chen et al, 2020;Giede-Jeppe et al, 2020;He et al, 2020;AltinbaŞ et al, 2021;Bi et al, 2021;Ferro et al, 2021;Gong et al, 2021;Hu et al, 2021;Huang et al, 2021;Lin et al, 2021). In a recent study, NLR ≥ 9 was an independent predictor of new in-hospital neurologic complications (Heuschmann et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Gong et al [ 66 ] reported that PLR (OR 1.013, 95% CI 1.009–1.016, P = 0.001) was an independent factor for early neurological deterioration post-thrombolysis. Chen et al[ 67 ] found that PLR was an independent predictor of 3-month functional outcomes in patients with acute ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, high platelet CD84 expression levels were associated with poor outcome in patients with stroke [ 48 ] PLR was inferior to NLR as predictor of outcome and severe neurological complications such as edema in a larger cohort study [ 28 ]. Nevertheless, in patients with stroke, namely those submitted to IVT, higher PLR was independently associated with unfavorable outcome and death at 3 months after thrombolysis, correlating with NIHSS and GCS [ 49 , 50 , 51 , 52 ]. Regarding psychiatric impairment, higher PLR was associated with post-stroke disorder, and depression 6 months after stroke [ 53 ].…”
Section: Resultsmentioning
confidence: 99%